Ensino e aprendizagem de guitarra em espaços músicoeducacionais diversos de João Pessoa - Garcia, Marcos da Rosa (2012)
The teaching and learning of the electric guitar have been consolidated from a conjuncture of factors related to the historical, cultural and interpretative development of the instrument. Thus, the formation of the guitar player was developed in different spaces and from individual strategies related to the practice and the social insertion of the electric guitar. Currently, the instrument has achieved new demands and new spaces, also reaching institutionalized dimensions with regard to its teaching. Therefore, we can say that nowadays the educational spaces for teaching and learning the electric guitar are constituted by formalized contexts and several other universes of practice and, consequently, of musical formation. Taking this scenario into consideration, I conducted a multicase study in the city of Joao Pessoa considering three important contexts of teaching and learning the electric guitar today. The investigated spaces were: graduation courses of music at the Federal University of Paraiba, the school of music Studio Musical, a private school that offer free courses of the instrument, and private lessons with a teacher who gives classes in his own residence. Taking this research as a basis, this study presents, discusses and analyzes key aspects that characterize electric guitar lessons in the three investigated spaces of musical formation, especially in relation to infrastructure, content, methodologies and different strategies used for teaching and learning. The methodological approach of the research was based mainly on qualitative procedures of data collection and analysis, but also contemplated quantitative instruments to enrich the understanding of the universe studied. Thus, throughout the investigative work, bibliographic studies, semi-structured interviews, questionnaires and participant observation of classes were carried out. From the results obtained, it was evident that, in all of the three contexts investigated, it is common the use of scales and the formation and use of chords and arpeggios as the basis for the practice of the instrument. However, each context presents singularities regarding the use of repertoire as a guiding element of learning, the availability of equipment to carry out the lessons and the systematic structuring of the contents applied.